2017
DOI: 10.1186/s13045-016-0383-x
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of DC-SIGNR in colon cancer cell adhesion, migration, invasion, and liver metastasis

Abstract: BackgroundTumor metastasis is an essential cause of the poor prognosis of colon cancer. DC-SIGNR is a C-type lectin that is frequently found on human liver sinusoidal endothelial cells. LSECtin, which is a homologue of DC-SIGNR, has been demonstrated to participate in colon cancer liver metastasis. Due to the similarities in the expression pattern and structure of the two proteins, we speculated that DC-SIGNR could also be involved in this process.MethodsColon cancer cells were treated with the DC-SIGNR protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 57 publications
1
39
2
Order By: Relevance
“…Subsequently, a gradual increase in the genesis of hepatic sinusoids and the surrounding vasculature may provide sufficient nutrition and oxygen proportional to the growth of the tumor, whilst allowing it time to adapt to the immune pressures of the host environment. Furthermore, it has been demonstrated that CLEC4M enhances the mobility and invasiveness of tumor cells in gastric and colon cancer (13,21). Additionally, high CLEC4M expression in HCC tissues is associated with a poorer prognosis, which is consistent with previous literature on lung (38) and cervical cancer (39).…”
Section: Clec4m Expression ------------------------------------------supporting
confidence: 88%
See 1 more Smart Citation
“…Subsequently, a gradual increase in the genesis of hepatic sinusoids and the surrounding vasculature may provide sufficient nutrition and oxygen proportional to the growth of the tumor, whilst allowing it time to adapt to the immune pressures of the host environment. Furthermore, it has been demonstrated that CLEC4M enhances the mobility and invasiveness of tumor cells in gastric and colon cancer (13,21). Additionally, high CLEC4M expression in HCC tissues is associated with a poorer prognosis, which is consistent with previous literature on lung (38) and cervical cancer (39).…”
Section: Clec4m Expression ------------------------------------------supporting
confidence: 88%
“…Several studies have demonstrated the involvement of CLEC4M in colon and gastric cancer progression. For example, CLEC4M is associated with poor prognosis in patients with colon cancer, and it is involved in the adhesion, migration, invasion and liver metastasis of colon cancer cells (21). Furthermore, CLEC4M exerts these biological functions through the signal transducer and activator of transcription 5/long non-coding RNA Heterogeneous Nuclear Ribonucleoprotein K Pseudogene 2/ C-X-C chemokine receptor type 4 axis (13).…”
Section: High Expression Levels Of Clec4m Indicate Poor Prognosis In mentioning
confidence: 99%
“…For the reactome pathway enrichment analysis, the upregulated genes mostly focused on regulation of the immune system and inflammation and cancer cell invasion and metastasis [36,37]. The downregulated genes played important roles in CRC-related pathways involving in preneoplastic lesions, carcinogenesis, metastasis, and poor prognosis [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is one of the most common malignancies of gastrointestinal system (1). Although the treatment of CRC has been developed substantially in the past decades, the prognosis of CRC remains unsatisfactory (2,3). Therefore, there is still an urgent clinical need to explore new and effective drugs for the treatment of CRC.…”
Section: Introductionmentioning
confidence: 99%